SARS-CoV-2 vaccination does not induce relapses of patients with inflammatory bowel disease - Elkharsawi, Ahmed; Arnim, Ulrike von; Schmelz, Renate; Sander, Cornelia; Stallmach, Andreas; Teich, Niels; Walldorf, Jens; Reuken, Philipp A. (Zeitschrift für Gastroenterologie, 2022)
Background Vaccination against SARS-CoV-2 is a promising strategy to protect immunocompromised IBD patients from a severe course of COVID-19. As these patients were excluded from initial clinical vaccination trials, patients frequently express concerns regarding the safety of these vaccines, especially whether vaccination might trigger IBD flares (“hit-and-run-hypothesis”).Methods In order to assess the risk of an IBD flare after vaccination against SARS-CoV-2, an anonymous survey was performed at five German IBD centers and one patient organization (Deutsche Morbus Crohn/Colitis ulcerosa Vereinigung (DCCV) e.V.) in August and October 2021.Results The questionnaire was answered by 914 patients, 781 of whom reported a previous vaccination against SARS-CoV-2 (85.4%). Vaccination against SARS-CoV-2 was not associated with an increased risk of IBD flares (p=0.319) or unscheduled visits to the IBD physician (p=0.848). Furthermore, typical symptoms of an IBD flare including abdominal pain, increases in stool frequency, or rectal bleeding were not influenced by the vaccination.Conclusion Vaccination against SARS-CoV-2 is safe in IBD patients. These results may help to reduce fears regarding the vaccination in IBD patients. Our results can help to reduce fears in IBD patients regarding the SARS-CoV-2 vaccine. A close communication between patients and physicians before and after the vaccination may be beneficial.
Keywords: IBD; Impfung; SARS-CoV-2; COVID-19; Nebeneffekt